Mapuche people, coup d'état and military dictatorship in the 'Historical Truth' Report: graduation of perspectives - Oteíza, Teresa; Arancibia, María Cristina (Árboles y Rizomas, 2023)
This study explores the construction of dialogicity regarding the 'historical truth' about the Mapuche people and the impact of the 1973 coup d'état and the dictatorship that was installed in Chile until 1990, in the Report of the Historical Truth Commission and New Deal with Indigenous Peoples (2008). With the aim of understanding how the intersubjective dialogue is discursively constructed, we examine the assembly between the discursive semantic systems of engagement and appraisal and its realization in the modality and mood systems, as lexicogrammatical systems that groups the expression of the speakers' judgments regarding the status of the exchanged merchandise and the interlocutor. The analysis shows that judgments regarding the 'historical truth' tend to be expressed metaphorically, through a medium and low probability with objective orientation, which engages in a restricted way with the 'historical truth' presented in the official document. Likewise, dialogicity that consistently constructs high degrees of probability tends to contract the heteroglossic space.
Keywords: APPRAISAL; ENGAGEMENT; interpersonal grammatical metaphors; Mapuche people; Commission of Historical Truth and New Treatment with Indigenous Peoples